2012
DOI: 10.1172/jci61492
|View full text |Cite
|
Sign up to set email alerts
|

ERK3 signals through SRC-3 coactivator to promote human lung cancer cell invasion

Abstract: In contrast to the well-studied classic MAPKs, such as ERK1/2, little is known concerning the regulation and substrates of the atypical MAPK ERK3 signaling cascade and its function in cancer progression. Here, we report that ERK3 interacted with and phosphorylated steroid receptor coactivator 3 (SRC-3), an oncogenic protein overexpressed in multiple human cancers at serine 857 (S857). This ERK3-mediated phosphorylation at S857 was essential for interaction of SRC-3 with the ETS transcription factor PEA3, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
195
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(216 citation statements)
references
References 39 publications
12
195
2
Order By: Relevance
“…Therefore, it is tempting to speculate that a MyoD-USP20-ERK3 signaling pathway may play a role in skeletal muscle differentiation and physiology. Recent studies have shown that ERK3 stimulates the migration of lung and breast cancer cell lines (13,15). In agreement with these findings, we found that ERK3 overexpression increases the migration of HeLa cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, it is tempting to speculate that a MyoD-USP20-ERK3 signaling pathway may play a role in skeletal muscle differentiation and physiology. Recent studies have shown that ERK3 stimulates the migration of lung and breast cancer cell lines (13,15). In agreement with these findings, we found that ERK3 overexpression increases the migration of HeLa cells.…”
Section: Discussionsupporting
confidence: 92%
“…USP20 regulates cell adhesion and migration through ERK3. ERK3 has been proposed to regulate actin cytoskeleton dynamics and to promote cellular migration in various cell types (13)(14)(15). We therefore investigated the possible effect of USP20 on these cellular responses and the contribution of ERK3.…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, mice with SRC-3 deletion had suppressed oncogene-and carcinogen-induced breast cancer initiation, progression, and metastasis (Kuang et al, 2004;Yi et al, 2013). Moreover, overexpression of SRC-3 has been frequently observed in a variety of other cancer types including lung, ovarian, liver, colorectal, pancreatic, and prostate cancers (Long et al, 2012;Palmieri et al, 2013;Geng et al, 2013). However, the biological function of SRC-3 in bladder cancer remains unexplored until now.…”
Section: Introductionmentioning
confidence: 92%
“…Multiple kinases tend to modulate SRC-3 activity through various PTM codes, demonstrating the global role of SRC-3 in integrating upstream signaling events to promote aggressive progression in breast cancer. In addition to ER and PR, SRC-3 functionally activates other breast oncogenic transcription factors such as NFκB, PEA3, and IKK, and facilitates transcriptional upregulation of cancer-specific genes (21, 22, 27). Common downstream targets affected by SRC-3 activation include the insulin-like growth factor-1 (IGF1) pathway, cyclin D1, and MMPs (15).…”
Section: The Role Of Nuclear Receptor Coactivators In Human Disease Amentioning
confidence: 99%